2018
DOI: 10.1021/acschemneuro.8b00543
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Efficacy of a Sigma 2 Receptor/TMEM97 Modulator (DKR-1677) after Traumatic Brain Injury

Abstract: Compounds targeting the sigma 2 receptor, which we recently cloned and showed to be identical with transmembrane protein 97 (σ2R/TMEM97), are broadly applicable therapeutic agents currently in clinical trials for imaging in breast cancer and for treatment of Alzheimer’s disease and schizophrenia. These promising applications coupled with our previous observation that the σ2R/TMEM97 modulator SAS-0132 has neuroprotective attributes and improves cognition in wild-type mice suggests that modulating σ2R/TMEM97 may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 33 publications
1
43
0
Order By: Relevance
“…Previous studies in cancer cells showed that a number of Sigma 2 receptor ligands induce apoptosis and cytotoxicity by generating reactive oxygen species [8,26]. On the other hand, Sigma 2 receptor antagonists are shown to provide a protective effect following traumatic brain injury [27]. Our study extended these findings and showed that TMEM97 played a protective role in RPE against oxidative stresses, providing a potential drug target to alleviate RPE degeneration in AMD.…”
Section: To Enablesupporting
confidence: 77%
“…Previous studies in cancer cells showed that a number of Sigma 2 receptor ligands induce apoptosis and cytotoxicity by generating reactive oxygen species [8,26]. On the other hand, Sigma 2 receptor antagonists are shown to provide a protective effect following traumatic brain injury [27]. Our study extended these findings and showed that TMEM97 played a protective role in RPE against oxidative stresses, providing a potential drug target to alleviate RPE degeneration in AMD.…”
Section: To Enablesupporting
confidence: 77%
“…Notably, σ2R is involved in several disease states, and the utility of its exogenous ligands as cancer therapeutics and diagnostic tools has been reported [15][16][17]. Additionally, σ2R has been implicated in multiple neurodegenerative and neurological disorders [18,19]. Similar to the ligands of σ1R, certain molecules that bind to σ2R also reduce mechanical hypersensitivity in a spared nerve injury model [20].…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation may shed new lights on BRD2-dominated transcription programs that sensitively respond to cholesterol level changes. Along this line, studies on BETs and S2R, both targets of increasing clinical (trial) drugs 6,13,24,36,37 , may synergize interventional opportunities for cholesterol-associated pathological conditions.…”
Section: Discussionmentioning
confidence: 99%